The Economic burden of Neonatal Intensive Care Unit Admission at a Community Hospital of Central Nepal - Sharma, Samana; Chapagain, Ram Hari; Pathak, Om Krishna; Gupta, Arun; Rai, Kavi Raj; Karn, Shruti; Sah, Sandeep Kumar (Journal of Nepal Paediatric Society, 2020)
Introduction: Neonatal sepsis is the commonest cause of neonatal morbidity and mortality and remains a major public health problem especially in developing countries. It is one of the most common causes for admission to neonatal units. The objective of this study was to evaluate the cost of care of neonates admitted in Neonatal Intensive Care Unit. It also compared the cost of care of neonates with sepsis and those with non-sepsis along with the duration of hospital stay and its correlation. Method: A hospital based prospective cross-sectional observational study was carried out over a period of one year. All the neonates admitted at NICU and fulfilling the inclusion criteria formed the study population. Total cost was calculated as the summation of direct and indirect cost. Normally distributed data was analyzed using the Student’s t-test, non-normally distributed data using Mann-Whitney U test. P-value < 0.05 was taken to be statistically significant. Result: Direct cost comprises more than two third of the cost. The median total cost of care of neonates admitted in NICU was USD 222.66 (Range 169.52-280.03). The cost for the ones with sepsis was USD 226.30 (Range 172.19-291.34) and 174.02 (Range 99.67-221.96) in non-sepsis. The mean duration of stay in NICU of the ones having sepsis was 6.6 days and 4.4 days in non-sepsis. Conclusion: The median total cost of care of neonates admitted in NICU was USD 222.66 (Range 169.52-280.03). The duration of stay and the total cost of treatment with sepsis are higher than those with non-sepsis.